2020
DOI: 10.1016/j.cub.2019.11.068
|View full text |Cite
|
Sign up to set email alerts
|

STRIPAK Limits Stem Cell Differentiation of a WNT Signaling Center to Control Planarian Axis Scaling

Abstract: Highlights d mob4 of the STRIPAK complex limits body size in planarians d wnt1+ posterior signaling-center cells promote tail size during regeneration d mob4 limits differentiation of wnt1+ pole cells from stem cells d Production of specialized signaling cells regulates organ size in regeneration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
5
26
0
Order By: Relevance
“…Wnt expression has been previously characterized within muscle tissue in acoels and planarians (Witchley et al, 2013;Raz et al, 2017;Scimone et al, 2017). In planarians, whereas the expression of Wnt ligands required for posterior identity (wnt-1 and wntP-2) is highly enriched in muscle tissue (Witchley et al, 2013), signaling centers are established in both anterior-and posterior-facing wounds in a stem-cell-dependent manner, suggesting a role for stem cells in controlling polarity of regenerating tissues in planarians (Vá squez-Doorman and Petersen, 2014;Lander and Petersen, 2016;Schad and Petersen, 2020). In cnidarians, Wnt ligands are expressed within both endodermal and ectodermal epithelial cells and Wnt3 protein is activated and secreted by interstitial stem cells upon amputation (Chera et al, 2009;Lengfeld et al, 2009;Nakamura et al, 2011;Petersen et al, 2015;Siebert et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt expression has been previously characterized within muscle tissue in acoels and planarians (Witchley et al, 2013;Raz et al, 2017;Scimone et al, 2017). In planarians, whereas the expression of Wnt ligands required for posterior identity (wnt-1 and wntP-2) is highly enriched in muscle tissue (Witchley et al, 2013), signaling centers are established in both anterior-and posterior-facing wounds in a stem-cell-dependent manner, suggesting a role for stem cells in controlling polarity of regenerating tissues in planarians (Vá squez-Doorman and Petersen, 2014;Lander and Petersen, 2016;Schad and Petersen, 2020). In cnidarians, Wnt ligands are expressed within both endodermal and ectodermal epithelial cells and Wnt3 protein is activated and secreted by interstitial stem cells upon amputation (Chera et al, 2009;Lengfeld et al, 2009;Nakamura et al, 2011;Petersen et al, 2015;Siebert et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By 48-72h post-amputation, the anterior pole forms at the pre-existing midline where it acts as a signaling center to influence ML and AP pattern in the blastema [23,24,26,57,58]. This time of regeneration is subsequent to the generic wound-response phase when notum is activated at anterior-facing wounds in pre-existing muscle cells.…”
Section: Anterior Axis Splitting In Activin-2 Rnai Animals Is Associamentioning
confidence: 99%
“…These observations point to the existence of mechanisms coordinating stem cell division, cell death, and organismal growth. Although recent studies have revealed some of the genetic pathways that control these processes (Oviedo et al, 2008a;Bender et al, 2012;Miller & Newmark, 2012;Peiris et al, 2012;Tu et al, 2012;Almuedo-Castillo et al, 2014;Lin & Pearson, 2014;Lin & Pearson, 2017;de Sousa et al, 2018;Arnold et al, 2019;Pascual-Carreras et al, 2020;Schad & Petersen, 2020;Ziman et al, 2020), it is not yet clear how cell number is "counted" or attuned to metabolic cues to effect rapid transitions between growth and degrowth.…”
Section: Introductionmentioning
confidence: 99%